Effect of concrete composition on splitting-cracks in prestressed concrete railroad ties: application of fracture mechanics - Shafiei Dastgerdi, Aref (Kansas State University, 2019)
In this study, the effect of concrete composition on end-splitting cracks in prestressed concrete members was investigated. Splitting cracks sometimes occur when prestressing force is introduced at de-tensioning and high stress-concentrations form around wire within transfer length. Transfer length is the bonded length required to fully introduce the prestressing force into the prestressed concrete member. Splitting cracks have been a recurring issue in prestressed concrete railroad ties where concrete cover is typically low. To prevent these splitting failures, the prestressed cross-section, wire type and concrete material properties, should be carefully evaluated to ensure satisfactory performance. With respect to the concrete member, the concrete material needs to be resistant to crack growth at the strengths at which the pretensioned member is detensioned. In this study, the effect of different concrete parameters including aggregate shape and content, water-to-cementitious (w/cm) ratio, fly ash, paste and air void content on the crack resistance of concrete used in concrete railroad ties were investigated using the Two-Parameter Model (TPM). For each mixture evaluated, twelve plain concrete prisms were tested in three-point bending at 4000, 6000 and 8000 psi concrete compressive strengths (27.5, 41.3 and 55.1 MPa) to determine the effect of concrete compressive strength on crack growth potential. In addition, splitting tensile tests were conducted on three samples at each compressive strength for all mixtures. Finally, the results were analyzed, and the results of each utilized method was discussed. The results show that increasing angularity, aggregate size distribution, and decreasing w/cm ratio improve fracture toughness by as much as 28% whereas changing paste, fly ash and air void content negligibly influence fracture toughness. However, all improving factors were seen to be most effective at low strengths. Statistical analysis conducted on fracture parameter values and concrete parameters indicated a correlation by which a statistical model for fracture-toughness prediction was developed. Next, the most beneficial factors on fracture toughness were incorporated to make and test actual pre-tensioned concrete prisms. Mixtures including the most effective factors were designed and pre-tensioned prisms with three different reinforcement edge distances (0.750, 0.625 and 0.500 in.) were fabricated and detensioned when the concrete compressive strength reached 4500 psi. Next, splitting cracks were quantitatively assessed by direct measurement. The results indicated a strong correlation between fracture toughness and crack length measurements. Additionally, a nonlinear regression model was developed predicting splitting-crack growth in prestressed cross-sections with varied edge-distance thickness. Finally, the effect of transvers reinforcement was investigated and a novel application of polymer fiber was proposed. The results obtained from this study could lead to a significant improvement in splitting crack resistance in pre-tensioned concrete members where high amount of transverse stress is often introduced at low compressive strengths.
Keywords: Prestressed concrete; Splitting crack; Aggregate; Mix design; Concrete railroad ties; ReinforcementFracture toughness